Ischemic preconditioning improves time trial performance at moderate altitude - Paradis-Deschênes, P.; Joanisse, D. R.; Billaut, F. (Medicine & Science in Sports & Exercise, 2018)
Purpose Endurance athletes often compete and train at altitude where exercise capacity is reduced. Investigating acclimation strategies is therefore critical. Ischemic preconditioning (IPC) can improve endurance performance at sea level through improved O2 delivery and utilization, which could also prove beneficial at altitude. However, data are scarce, and there is no study at altitudes commonly visited by endurance athletes.